Analyzing the combustion oscillation of a gas turbine for syngas based on the characteristic time-scale theory. (1st May 2022) - Mu, Yanfei; Li, Zongyan; Luo, Kun; Fan, Jianren; Xing, Jiangkuan; Zhang, Bo; Shi, Shaoping
Highlights: The combustion oscillation problem of a gas turbine for syngas is affected by the ignition delay time. The mathematical model for the ignition delay time of the wet syngas combustion is established. Two operational measures to reduce combustion oscillations are proposed and tested effectiveness. Abstract: When the ambient temperature is less than −10 °C in winter, the gas turbine for syngas in Huaneng Tianjin integrated gasification combined cycle (IGCC) power station has an evident combustion oscillation phenomenon, which seriously affects the production safety and efficiency. This study used the characteristic time-scale theory to guide the operation, thereby reducing the combustion oscillation of the gas turbine for syngas. The work progressed as follows. First, the boundaries of the combustion oscillation and maximum temperature safe limitations were defined based on the operational data from the extreme ambient temperature in summer and winter in the Huaneng Tianjin IGCC power station. Then, the mathematical model of combustion with critical parameters, such as ignition delay time, the adiabatic temperature of the flame, and flame speed, was constructed using the binary quadratic regression method under various combinations of dry syngas, natural gas, and steam flow rates. Finally, an operation scheme for reducing the combustion oscillation of the gas turbine for syngas in winter was designed, as well as the limitation boundary and computation model. This operation scheme can effectively reduce the combustion oscillation in winter; this was confirmed in actual operation. The results of this study should assist gas turbine designers in improving the safety, reliability, and stability of syngas turbines.